Critical remark on multi-criteria approach to corporate auditing risk assessment - evidence from Brazil. (2016) - Imoniana, Joshua Onome; Gartner, Ivan Ricardo
Audit risk assessment concerns establishing a confidence level for engagement, thereby enhancing the detection of RMM and in so doing assisting the selection of mitigating procedures. This study examines the risk evaluating approaches predominantly adopted by big-4 and the second tier firms and proposes a CARM using the multi-criteria approach. In order to support the said objective one draws on the following philosophical premise: corporate audit risk is a sum of service risk and auditing risk whose values scaled by multi-criteria assessment results a reliable auditor value judgment. Upon simulating the model, results show that on one hand, audit partners would only accept audit services with low service risk and on the other hand, audit proposal that conjugates significant and very significant ethical risk; moderate, significant and very significant moral risk; moderate, significant and very significant loss of earning risks; would be treated with extreme due professional care by auditors.